2023
DOI: 10.1002/cnr2.1822
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability and its effect on cell lines

Abstract: Background Cancer cell lines are invaluable model systems for biomedical research because they provide an almost unlimited supply of biological materials. However, there is considerable skepticism regarding the reproducibility of data derived from these in vitro models. Recent findings Chromosomal instability (CIN) is one of the primary issues associated with cell lines, which can cause genetic heterogeneity and unstable cell properties within a cell population. Many of these problems can be avoided with some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The spindle phenotypes we observed in Pan2KD cells treated with colchicine coupled with their decreased cell viability suggested these cells could have undergone abnormal chromosome segregation. Cells with mis-segregated chromosomes often have abnormal nuclei and have increased cell death (57–59). An imaging based whole-genome siRNA screen in HeLa cells found that the absence of PAN2 led to irregular nuclear shape and chromosome mis-segregation (60).…”
Section: Discussionmentioning
confidence: 99%
“…The spindle phenotypes we observed in Pan2KD cells treated with colchicine coupled with their decreased cell viability suggested these cells could have undergone abnormal chromosome segregation. Cells with mis-segregated chromosomes often have abnormal nuclei and have increased cell death (57–59). An imaging based whole-genome siRNA screen in HeLa cells found that the absence of PAN2 led to irregular nuclear shape and chromosome mis-segregation (60).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic manipulation to produce immortalized cell lines has been associated with increased genomic instability (i.e. a state in which genomic mutations occur at higher frequency), including chromosomal instability (defined as a cellular state during in which unwarranted chromosomal changes in number and structure occurring at a high rate) [ 32 , 45 ]. As a consequence IDECL may become unstable and heterogeneous (within and between different laboratories), resulting in skewed and unreproducible results.…”
Section: Main Textmentioning
confidence: 99%
“…The cells may undergo rapid epigenetic and transcriptional changes [ 108 ], differentiate [ 109 ], lose the expression of certain genes [ 110 ], change the biophysical properties of the cell membrane [ 111 ], lose sensitivity to oxidative stress [ 112 ], and undergo many other alterations. Conventional 2D cell lines lack polarity and their contact with tumor environment is affected [ 4 ], they are chromosomally unstable [ 3 ], and they do not preserve the heterogeneity and complexity of the tissue of origin. The heterogeneity of the tumor is currently described not only as a difference between the cancer cells in morphology, transcriptional profiles, and metabolism, but also includes the differences between the tumor microenvironment, which plays an important role in tumor resistance to therapy, the higher level of metastasis, and aggressiveness [ 113 , 114 , 115 ].…”
Section: In Vitro Models Of Neuroblastomamentioning
confidence: 99%
“…However, none of the preclinical cancer models are ideal. The extent of the clinical relevance of the existing models has been a long-standing problem in cancer research [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%